Education Program B2SA Goes to School of Knowledge Level and Habit Bring Meal - Wahyu Tri Astuti; Evy Tri S; Novida Prima W; Emah Marhamah; Lis Nurhayati; Agus Setiyawan; Indah Tri C; M Wanda Fata (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: The food consumption pattern of the community including school children until now still shows a tendency of less diversity in terms of food types and nutritional balance. This B2SA (Beragam, Bergizi, Seimbang, Aman) food consumption pattern functions to direct food utilization patterns to meet the standards of quality, diversity, nutritional content, safety and halal, in addition to efficiency to prevent waste in daily household expenses. Objective: To determine the effect of education about B2SA Goes To School on knowledge level and habits bring meal boxes in 7th grade students at SMP Negeri 1 Magelang City. Method: Quasi Experiment design, the research design used is quantitative with one group pre posttest without control, a population of 256 class VII students, a sample of 152 students with purpose sampling, the instrument uses a pre and post questionnaire on B2SA knowledge and habits bring meal boxes. Bivariate analysis using the non-parametric Wilcoxon test. Results: There is a significant difference between knowledge level pre-intervention and post-intervention as shown in the Wilcoxon analysis with a significance result of p-value = 0.000 (0.05) meaning that there is a significant influence of education about B2SA Goes To School on increasing student knowledge and regarding the influence of education about B2SA Goes To School on the habit of bringing food, a significance value of ρ-value = 0.000 was found, which means that there is a significant difference in the habit of bringing supplies before and after education about B2SA Goes To School. Conclusion: There is an influence between education about B2SA Goes To School on the habit of bringing food and the habit of bringing school supplies at SMP Negeri I Kota Magelang.